2015
DOI: 10.1002/ange.201410779
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Activation using DNA‐Based Logic Gates

Abstract: Oligonucleotide‐based molecular circuits offer the exciting possibility to introduce autonomous signal processing in biomedicine, synthetic biology, and molecular diagnostics. Here we introduce bivalent peptide–DNA conjugates as generic, noncovalent, and easily applicable molecular locks that allow the control of antibody activity using toehold‐mediated strand displacement reactions. Employing yeast as a cellular model system, reversible control of antibody targeting is demonstrated with low nM concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
(29 reference statements)
0
24
0
Order By: Relevance
“…First, the product of the exchange reaction BI can form a bivalent interaction with its target antibody, thus making the displacement of O by I thermodynamically more favourable. We recently showed that bivalent peptide-dsDNA ligands form very tight 1:1 complexes with their target antibody, showing a 500-fold increase in affinity compared to the monovalent peptide-antibody interaction 33 34 . Second, the colocalization of the reactants increases their effective concentration, hence enhancing the rate of the exchange reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the product of the exchange reaction BI can form a bivalent interaction with its target antibody, thus making the displacement of O by I thermodynamically more favourable. We recently showed that bivalent peptide-dsDNA ligands form very tight 1:1 complexes with their target antibody, showing a 500-fold increase in affinity compared to the monovalent peptide-antibody interaction 33 34 . Second, the colocalization of the reactants increases their effective concentration, hence enhancing the rate of the exchange reaction.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure minimal background in combination with fast initiation of the ATSE reaction, we optimized the design by systematically increasing the length of the toehold T from 0 to 6 nucleotides, hence gradually destabilizing the initial state. The length of the strands was chosen such that the bivalent peptide-dsDNA product BI contained 24 basepairs, a length that we have previously shown to be optimal for bivalent binding to the target antibody 33 34 . In the absence of input antibody no increase in fluorescence was observed up to a toehold length of 3 nucleotides ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Synthetic oligonucleotides can also be conjugated with other recognition elements responding to a wide range of proteins and biomolecules, further broadening the potential interface between the world of synthetic nucleic acids and proteins. Recently, we and others have, for example, employed antigenconjugated synthetic DNA strands to allow programmable interactions with specific antibodies [27][28][29][30][31] that control the assembly and disassembly of DNA-based molecular structures. 32 In the above-described examples, the communication is limited to protein-to-DNA interactions in which a specific protein (e.g., a transcription factor, an enzyme, or an antibody) triggers a functional event in a structure built of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic nucleic acid strands can be used as molecular scaffolds to append different recognition elements that allow the design of nucleic acid probes responsive to a wide range of targets. [15][16][17][18][19] In a demonstration of such potentiality, we and others have recently employed antigen-conjugated nucleic acids rationally designed to respond to clinically-relevant antibodies. [19][20][21][22][23] Motivated by the above considerations, we demonstrate here a cell-free diagnostic platform for the detection of specific antibodies in blood serum based on the use of antibody-responsive nucleic acid transcriptional switches.…”
Section: Introductionmentioning
confidence: 99%